Practical financial statement analysis - Foulke, Roy Anderson (New York : McGraw-Hill, 1968)
The volume will be of the widest possible practical help to business executives, industrial engineers, bank credit executives, bank examiners, investment analyst, and mercantile credit managers in their everyday work, as well as to the steadily increasing number of students of the analysis of American business enterprises at universities, colleges, and business schools.
Includes bibliographical footnotes and index.
hza 30/08/2018
Loans
Keywords: Financial statements; Corporations